Lung cancer patients with nephropathy as the first manifestation: Literature review and clinical study report - Xu, Qianqian; Zou, Guming; Zhuo, Li; Gao, Hongmei; Li, Wenge (Frontiers in Oncology, 2022)
Background: To investigate the relationship between membranous nephropathy (MN) and lung cancer. Methods: To report patients with lung cancer detected by follow-up after the diagnosis of MN by renal biopsy in China-Japan Friendship Hospital from January 2010 to December 2019, and to study the prognosis of lung cancer-associated MN and have a review of the literature. Results: Lung cancer was detected in 6 patients followed for 1-27 months (median 8 months) after the diagnosis of MN: including 4 cases of lung adenocarcinoma, 1 case of carcinoma in situ, and 1 case of small cell lung cancer with multiple metastases. 5 cases were in remission after surgically resected and one case was remitted after chemotherapy. 6 patients were negative for serum anti-PLA2R antibodies, and glomerular IgG subclass deposition detected by immunofluorescence were all positive for IgG1 and IgG2. Glomerular PLA2R、THSD7A and NELL-1 staining were assessed in all 6 patients, one patient was positive for glomerular PLA2R staining, 2 patients were positive for glomerular THSD7A staining , and all patients were negative for NELL-1 staining. Literature review of the relationship between MN and lung cancer: 7 articles about cancer-associated MN were searched, reporting 32 cases of MN associated with lung cancer, among which 14 cases had nephropathy as the first manifestation, and only 5 patients had remission of MN after treatment of lung cancer . Conclusions: A few lung cancer patients have nephropathy as the first clinical manifestation, and MN can also be remitted after treatment of lung cancer .